Solar cells based on multicrystalline silicon - Popov, V.G. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
This review comprises modern publications devoted to problems of development and manufacturing photovoltaic solar energy converters (solar cells) based on block multicrystalline silicon (poly-Si). Methods of growing polysilicon ingots, mechanical and chemical treatment, characteristics of polysilicon depending on grain sizes and impurity-defect composition are considered. Methods of improving polycrystalline Si parameters (gettering, treatments in different ambients, passivating treatments) are analyzed. Basic design features of the poly-Si based solar cells and technological modes of their manufacturing are surveyed. It is shown that the efficiency value of such solar cells practically reaches that of similar devices manufactured using single-crystalline Si grown by the Czochralski method. Some problems of measurements of minority non-equilibrium charge carriers lifetime in polycrystalline material are surveyed.